Closing the Citizenship Gap in Canada's North: Indigenous Rights, Arctic Sovereignty, and Devolution in Nunavut - Adam Goldenberg; Tony Penikett (Michigan State University College of Law, 2013)
Article published in the Michigan State International Law Review.